MANAGEMENT OF THE SYSTEM «CDP DISPATCHER POWER SUPPLY SYSTEMS - PRODUCTION ENVIRONMENT» AS A TOOL FOR OPTIMIZATION OF WORKING CONDITIONS - Serikov, Y. (Municipal economy of cities. Series: «Economy science», 2022)
Ensuring industrial safety, labor protection, health of workers, including in the field of electricity, is an urgent task today. This task is set out in the development strategies of the European Union, the United States, Canada and others. This position of the states is aimed at reducing the level of occupational injuries and occupational diseases, which is high, especially in the field of electricity in almost all countries. Analysis of the state of the solution of this problem shows that the working conditions of the staff of the power supply system, especially in the central control points, in many cases need to be improved. The study of the relationships in the system «dispatcher of the main control point of power supply systems - production environment» confirms the importance of solving the problem of improving their working conditions. The peculiarities of power supply system managers are revealed, which are due to the following two main facts. 1 - production activity of dispatchers of the central dispatching points is characterized by the considerable list of tasks which differ in character of the performed work. This necessitates frequent switching of their activities. This mode of operation causes significant psychophysiological loads in their body. 2 - the state of health directly affects the health and well-being of dispatchers during the work shift. This is especially true in emergencies, which require the maximum concentration of professional knowledge, the attention of dispatchers in developing the necessary solution to restore power. Thus, the task of ensuring proper (regulatory) working conditions, regulated by regulations, is complemented by the need to develop measures to optimize the regime «work – rest» during the work shift, ergonomics of the workplace. In this case, for example, while ensuring proper microclimatic conditions, it is necessary to ensure their optimal parameters, and the design or improvement of artificial lighting systems should be based on the qualitative characteristics of light flux. That is, the organization of the production environment should be improved not only taking into account changes in regulations, but also taking into account the latest advances in ergonomics, other areas in the field of providing a comfortable working environment. Based on this, the solution of the problem requires a comprehensive system approach. This approach is proposed to be implemented using the developed adaptive management system of working conditions, ergonomics, ie in general, the production environment in the central control point of the power supply system. A software algorithm for such a management system is presented. The presented methodology for developing an adaptive management system is universal. It can be implemented in power supply systems for various purposes.